2021
DOI: 10.2147/jhc.s300382
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of On-Treatment Liver Stiffness for Hepatocellular Carcinoma Development in Patients with Chronic Hepatitis B

Abstract: Background: Dynamic changes in fibrosis markers occur under long-term antiviral treatment (AVT) for chronic hepatitis B. We evaluated prognostic values of on-treatment liver stiffness (LS) compared to ultrasonography findings and determined its optimal cutoff. Methods: The cumulative probability of hepatocellular carcinoma (HCC) was assessed among 880 patients receiving entecavir or tenofovir for ≥2 years. LS was measured using transient elastography.Results: After ≥2 years' AVT, the proportion of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Furthermore, along with the dynamic changes in APRI or FIB-4 index during AVT, assessment of transient elastography, which proved to have higher predictive efficacy after 12 months as an easier predictive algorithm, might give useful information. Actually, when we tried to stratify the risk of HCC development by the on-treatment LS value (cutoff value: 6.4 kPa) from the subgroup with available paired TE results (n = 1102, 36.4%) [18], we confirmed their significant association (p < 0.001). Hence, further large-scale study with the serial follow-up of transient elastography during long-term AVT should be required.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, along with the dynamic changes in APRI or FIB-4 index during AVT, assessment of transient elastography, which proved to have higher predictive efficacy after 12 months as an easier predictive algorithm, might give useful information. Actually, when we tried to stratify the risk of HCC development by the on-treatment LS value (cutoff value: 6.4 kPa) from the subgroup with available paired TE results (n = 1102, 36.4%) [18], we confirmed their significant association (p < 0.001). Hence, further large-scale study with the serial follow-up of transient elastography during long-term AVT should be required.…”
Section: Discussionmentioning
confidence: 77%
“…Meanwhile, other HCC prediction models using fibrosis parameters assessed during long-term AVT (i.e., modified REACH-B, CAGE-B, and SAGE-B scores) have also been introduced with promising results [16,17]. Most recently, given that baseline fibrosis and/or necro-inflammation can be partially modified or regressed through long-term AVT [18][19][20], Nam et al [21] recently suggested a novel HCC prediction model using fibrosis markers assessed at dual time points, named the Fibrosis marker response, Sex, Age, and Cirrhosis (FSAC) score. The model incorporates on-therapy changes, including a fibrosis index based on four factors (FIB-4) [22,23] and aspartate aminotransferase (AST)-to-platelet ratio index (APRI) [24] at 12 months, as well as sex, age, and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%